Flowering phenology and floral yield of four cultivated Jasminum species in Indonesia - PAWITRI ADHISTYANA MAYESTI; ANI KURNIAWATI; KRISANTINI KRISANTINI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Mayesti PA, Kurniawati A, Krisantini. 2025. Flowering phenology and floral yield of four cultivated Jasminum species in Indonesia. Biodiversitas 26: 6047-6055. Jasmine is one of the most important flowers in Indonesia and Asia, used mainly for fresh flowers, flavoring ingredients, and can be processed into cosmetics and essential oils. Despite the rich diversity of Indonesian jasmines, there are limited studies on the growth and flowering of various jasmine types. Understanding the characteristics of each type is crucial as a foundational step for the development and commercialization of jasmine. This study examined the morphology, flower phenology, and production of four types of jasmine: Jasminum sambac “Telur”, a local Java jasmine, “Emprit Bandar Arum”, and Bintang (Jasminum multiflorum). The study was conducted in an open field in East Java, Indonesia, at an elevation of 348 m above sea level. Each type of jasmine consists of 50 plants. Observations and measurements were conducted on leaf and flower morphology, flower phenology, and production cycles. The four types of jasmine showed diversity in fragrance, leaf arrangement, number of flowers, flower arrangement, and productivity. The local jasmine has single corollas, whereas jasmine “Telur” has multiple. Jasminum sambac “Telur” has the most significant and heaviest flower (595 mg), but produces significantly fewer flowers. Jasminum multiflorum Bintang flower weighs 24 mg, but produces 11 flowers per plant. The local jasmine and Emprit Bandar Arum flowers fall within the mid-range, i.e., 49-62 mg flower weight, and produce 11-17 flowers per plant. The flowering phenology of the four jasmines spans 7-14 days, with flower bud appearance and development taking 8-10 days, followed by enlargement and swelling for 2-4 days before anthesis. Flowers at anthesis are the most fragrant in all four types of jasmine, with local Jasmine standing out in floral fragrance and production. This information would be useful for identifying different jasmine types, determining the best uses, and the commercial production of these four types of jasmines.